(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Oxytocin is commonly used for induction of labor. The objective of the study was to assess the knowledge and practice regarding oxytocin administration during the first stage of labor in maternity ward. Method: A descriptive cross-sectional study was conducted among nurses of maternity ward of Patan Hospital, Nepal. Data was collected by using self-administered structured questionnaire for the knowledge assessment. Observation checklist was used to record the practice. Descriptive and inferential data analysis was done by SPSS version 16.The association and correlation between variables were measured by chi-square and Pearson correlation coefficient respectively. Result: Out of 31 nurse participants, majority (87.1%) had good knowledge and showed moderately good practice (in 70%) regarding oxytocin administration. The correlation between knowledge and practice on use of oxytocin among the staff nurses had positive relationship(r=0.051). Conclusion: Majority of nurses had good level of knowledge and moderate level of practice on use of oxytocin.